Qashash sebagai Materi dan Metode Pendidikan Akhlak: Kajian Tafsir QS al-Lahab - Nur Ali Subhan (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2019)
Surah Al-Lahb is in 111th surah of Quran that is Makki which means this surah was received by Rasulullah when he was still in Mecca. This surah tells about the uncle of Rasulullah namely Abu Lahab who came from high level family and tribes that make him arrogant and refusing da’wa of Rasulullah. Abu Lahab always made effort to do bad things in intriguing da’wa of Rasulullah and he wanted Rasulullah’s da’wa to be failed. His wife also helped him to do so. Because of that, Allah swt cursed him and his wife that they would be sent to the hell. Abu Lahab becomes one of surah name in Quran as a prove of history about the bad manner of Abu Lahab to Rasulullah. The method of Qisah (At-Tarbiyah bil al-Qishah) in this surah is one of interesting methods in education. This is way of Quran to explain about phropet and also others to give attention and take learning. This method brings big impact to increase curiousity and also intelligence of thinking because that every story has its own value. So, that will be easy for everyone to remember and understand. Finally, found there are three values of akhlak education in surah Al-Lahb that are lying, arrogance, and spite. That bad akhlak must be avoided provide bringing harm to ourselves, families, and society. Keywords: Al-Lahb, al-Qashash, akhlak education